Multimodality imaging of a pulmonary artery sarcoma. Issue 1 (26th November 2017) - Yeung, Darwin F.; Johnston, Angela; Simmons, Christine; Goddard, Karen; Dewar, Leith R.; Yee, John; Kelliher, Edel; Tsang, Michael Y. C.; Gin, Kenneth; Jue, John; Nair, Parvathy; Lee, Pui‐Kee; et al.
Abstract : Pulmonary artery sarcoma is a rare malignant neoplasm. Here, we describe a patient with a pulmonary artery sarcoma, which was only subtly visible and therefore not fully appreciated on initial transthoracic echocardiogram. Characterization of the tumor was aided by the use of multimodality imaging that included computed tomography, magnetic resonance imaging, and positron emission tomography. Familiarity with its appearance on multiple imaging modalities including echocardiography is important to ensure timely diagnosis, although the optimal treatment strategy is still unknown, and the prognosis remains poor.